Microalgal Diversity and its Role in Wastewater Treatment - Kumar, Rajiv (My University, 2012)
Present work highlights the role and application of microalgal diversity in wastewater stabilization ponds with its potential for treating wastewater in terms of removal of organic and inorganic pollutants and heavy metal remediation. Chlorella sp. was present as one of the most dominating species in wastewater stabilization pond during whole 10 months on-site study at village Sanghol, Distt. Fatehgarh Sahib, Punjab, India. The order of microalgal dominance was Chlamydomonas > Lyngbya > Diatoms, whereas Chlorococcum sp. and Closteriopsis sp. were also seen in the month of August and September besides cyanobacteria like Gloeocapsa and Myxosarcina. A marked reduction of 15 to 83% in BOD5 and 52 to 93% in COD from inlet wastewater after treatment represented effective treatment potential of wastewater stabilization ponds during complete sampling period. The stabilization ponds also demonstrated their metal remediation potential by reducing 72% and 73% removal of Zn2+ and Pb2+ especially in the months of November and March respectively. Metal removal studies carried out with pure culture of Chlorella sp. (R1) and consortium (CP1) developed from pond wastewater revealed their efficient metal removal potential where Chlorella sp. (R1) demonstrated maximum removal potential for Zn2+>Pb2+>Cr (total) whereas, consortium (CP1) removed maximum Zn2+ from medium followed by Cr (total) and Pb2+. Chlorella sp. (R1) which was found as most dominating in wastewater showed more resistance to metal contamination in comparison to earlier reported isolates with EC50 of 4.34 and 10.25 mg L-1 for total Cr and Zn2+ respectively, whereas Pb2+ was non toxic upto 20 mg L-1. Metal uptake capacity (qmax) of 33.31, 63.92 mg g-1 for Pb2+ and Zn2+ respectively by algal consortium (CP1) and 34.36, 41.75 and 60.7 mg g-1 for Pb2+, Zn2+ and total Cr by Chlorella sp. (R1) respectively demonstrated good metal uptake potential. Chlorella sp. (R1) was analysed for COD and BOD5 reduction under indoor conditions and it’s effective role in removal of Cr from electroplating industrial wastewater using immobilized alga in packed bed column showed its strong potential for development of commercial bioresin.
Keywords: Microalgae; wastewater; Heavy Metals; BOD